Physical Activity Resource and User Characteristics in Puerto Vallarta, Mexico (Recursos para la actividad física y características de los usuarios en Puerto Vallarta, México) - Soltero, Erica G.; Mama, Scherezade K.; Pacheco, Ann M.; Lee, Rebecca E. (Retos, 2015)
Abstract. Physical activity resources (PARs) are valuable settings for physical activity (PA) in Latin countries. PAR quality, amenities, and features are strongly associated with PA. However, the relationship between PAR characteristics and PAR usege has not been investigated in Mexico. This study aimed to describe and evaluate PARs and their association with PAR users and determine whether user and PAR characteristics differed by resource type, proximity to the ocean, or neighborhood socioeconomic status (SES) status in Puerto Vallarta, Mexico. Assessed PARs (N=8) included parks (N=5), a freestanding plaza (N=1), and plazas combined with a park (N=2).The Physical Activity Resource Assessment (PARA ©2010) was used to evaluate PAR amenities, features, and incivilities. The PARA was adapted to include plazas and open green spaces to reflect cultural and land use differences in Mexico. The System for Observing Play and Recreation in Communities (SOPARC) was used to code the age, gender, and ethnicity of each user. Descriptive analyses were used to describe PARs and users. Correlations among PAR characteristics and users were investigated. T-tests and one-way ANOVAs were used to determine whether PAR and user characteristics differed by PAR type. All PARs were accessible, free for use, about the size of a city block, and were on average, 1.9 kilometers from the water (SD=1.3, Range=.1-3.2).  PARs had an average of 4.4 amenities (SD=1.6), 2.5 features (SD=1.4), and 3.5 incivilities (SD=2.1). The quality of amenities (Range=0-39, M=11.0, SD=4.8) and features (Range=0-36, M=6.4, SD=3.6) was low, and severity of incivilities was high (Range=0-36, M=29.9, SD=4.1).  Eighty-one users (60.5% men) were observed, with plazas attracting more users (m=38.0) than parks (m=6.8) or combination resources (m=4.5). PAR users were mostly adults (59.2%), with some children (28.4%) and few adolescents (12.4%). The quality of amenities was correlated with the total number of users (r=.74, p=.04). There were no differences in count or quality of amenities, features, or incivilities (ps>.05) by resource type. The plaza attracted more women compared to parks and combination resources (F=15.84, df=2.5, p=.01). More adolescents (F=7.29, df=2.5, p=.03) and adults (F=14.64, df=2.5, p=.01) were observed at the plaza compared to the parks or combination resources. PARs were highly accessible, yet the presence and quality of amenities and features was poor and incivilities were high. Parks were most common; however, the plaza attracted the most users, including women, teens, and adults. Findings indicate that increasing the quality of amenities may be an effective strategy for promoting PA. Poor quality of amenities and features may have limited the ability to detect associations with users.Resumen. Antecedentes: Los recursos de actividad física (RsAF) son ámbitos de valor para la actividad física (AF) en los países latinos. La calidad, comodidades y características de los RAF están fuertemente asociadas con la AF. Sin embargo, la relación entre las características y el uso de los RAF no se han investigado en México. Objetivo: Este estudio tuvo como objetivo describir y evaluar los RAF y su asociación con los usuarios de los RAF, y determinar si los usuarios y las características de los RAF difieren por tipo de recurso, la proximidad al mar, o el nivel socioeconómico del vecindario, en el estado de Puerto Vallarta, México. Métodos: Los RsAF fueron evaluados (N = 8) incluyendo parques (N = 5), una plaza independiente (N = 1), y plazas combinadas con un parque (N = 2). La Evaluación de los Recursos de Actividad física (PARA © 2010) fue usada para evaluar las comodidades, las características y los actos incívicos de los RAF. El PARA fue adaptado para incluir plazas y espacios verdes para reflejar las diferencias culturales y el uso de la tierra en México. El Sistema de Observación de Juego y Recreación en Comunidades (SOPARC) se utilizó para codificar la edad, el género y la etnia de cada usuario. Los análisis descriptivos fueron usados   para describir los RsAF y los usuarios. Se investigaron las correlaciones entre los usuarios y las características de los RAF. Se utilizaron Pruebas T y un ANOVAs unidireccional para determinar si las características del usuario y las características de los RAF diferían según el tipo de RAF. Resultados: Todos los RAF eran accesibles, gratis para su uso, aproximadamente del tamaño de una manzana de la ciudad, y estaban, de promedio, a 1,9 km del agua (SD = 1.3, rango = .1-3.2). Los RAF tenían una media de 4.4 instalaciones (SD = 1.6), 2.5 características (SD = 1.4) y 3.5 actos incívicos (DE = 2.1). La calidad de las instalaciones (Rango = 0-39, M = 11.0, SD = 4.8) y características (rango = 0-36, M = 6.4, SD = 3.6) fueron bajas, y la gravedad de los actos incívicos fue alta (gama = 0- 36, M = 29,9, SD = 4.1). Ochenta y un usuarios (60.5% varones) fueron observados, las plazas atraen a más usuarios (m = 38.0) que los parques (m = 6.8) o recursos combinados (m = 4.5). Los usuarios de los RAF eran en su mayoría adultos (59.2%) con algunos niños (28.4%) y pocos adolescentes (12.4%). El número total de usuarios se correlacionó con la calidad de las instalaciones (r = 0,74, p = 0,04). No hubo diferencias en el recuento o la calidad de las instalaciones, características o actos incívicos (p> .05) por tipo de recurso. La plaza atrajo a más mujeres en comparación con los parques y los recursos combinados (F = 15,84, df = 2,5; p = 0,01). Más adolescentes (F = 7.29, df = 2.5; p = 3.) y adultos (F = 14.64, df = 2.5; p = .01) se observaron en la plaza frente a los parques o recursos combinados. Conclusiones: Los RAF eran muy accesibles, sin embargo, la presencia y calidad de instalaciones y servicios fue deficiente y los actos incívicos eran altos. Los parques fueron más comunes; sin embargo, la plaza atrajo la mayor cantidad de usuarios, incluidas las mujeres, adolescentes y adultos. Los resultados indican que el aumento de la calidad de las instalaciones puede ser una estrategia eficaz para promover la AF. La mala calidad de las instalaciones y servicios puede haber limitado la capacidad de detectar asociaciones con los usuarios.